SYSTEMATIC LITERATURE REVIEW CASH WAKAF LINKED SUKUK - khusnun mufidah; Rakhmawati (Universitas Islam Indonesia, 2023)
This study aims to determine the trend and topic of research on Cash Waqf Linked Sukuk (CWLS) published from 2018 to 2022 on the Google Scholar database. This study uses both quantitative and qualitative. The qualitative analysis used is the systematic literature review (SLR) analysis. Based on the search results, 76 documents were exported in RIS format and processed using VOSviewer. The analysis results show that the trend of research on CWLS from 2018-2022 can be grouped into three clusters. The focus of the research content can be categorized into 21 topics, with the most discussed topics about the development of CWLS, the potential of CWLS to finance economic recovery after the COVID-19 pandemic, and the role of CWLS on economic development. The author who contributed the most was Hendri Tanjung, with three publications. Most of the published research is in the form of journals as many as 62 studies. The literature study is the most widely used research method, with as many as 43 studies